2016
DOI: 10.1523/jneurosci.1857-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Border-Ownership Cells across Artificial Stimuli, Natural Stimuli, and Stimuli with Ambiguous Contours

Abstract: Segmentation and recognition of objects in a visual scene are two problems that are hard to solve separately from each other. When segmenting an ambiguous scene, it is helpful to already know the present objects and their shapes. However, for recognizing an object in clutter, one would like to consider its isolated segment alone to avoid confounds from features of other objects. Border-ownership cells (Zhou et al., 2000) appear to play an important role in segmentation, as they signal the side-of-figure of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 50 publications
5
46
0
Order By: Relevance
“…Thus, indirect evidence of figure-ground modulation of natural images could be retrieved in the activity of multiple areas of the visual processing stream. This is consistent with a recent study, which reported that border-ownership of natural images cannot be resolved by single cells, but requires a population of cells in monkey V2 and V3 (Hesse JK and DY Tsao 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, indirect evidence of figure-ground modulation of natural images could be retrieved in the activity of multiple areas of the visual processing stream. This is consistent with a recent study, which reported that border-ownership of natural images cannot be resolved by single cells, but requires a population of cells in monkey V2 and V3 (Hesse JK and DY Tsao 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, from an experimental viewpoint, the role of visual segmentation has been demonstrated only by means of non-ecological stimuli (e.g., binary figures, random dots, oriented line segments and textures). Although two recent studies investigated border-ownership in monkeys with both artificial and natural stimuli (Hesse JK and DY Tsao 2016;Williford JR and R von der Heydt 2016), a proof of the occurrence of foreground-background segmentation in the human brain during visual processing of naturalistic stimuli (e.g., natural images and movies) is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…which specific electrodes, filtering regime and others). The relevant region within Fig 7E (indicated by black rectangular outline) presents substantial modulations (reflected by red tint) between 30 ms and 70 ms. More accurate estimates of the timescale involved will require further EEG investigations combined with relevant single-unit measurements [ 53 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…For a more detailed operational definition of how border-ownership selectivity is determined experimentally, see Section 2.4. Border-ownership coding has been studied using a wide variety of artificial stimuli, including those defined by luminance contrast, color contrast, figure outlines (Zhou et al, 2000), motion (von der Heydt et al, 2003), disparity (Zhou et al, 2000; Qiu and von der Heydt, 2005), and transparency (Qiu and von der Heydt, 2007) as well as, more recently, with faces (Hesse and Tsao, 2016) and within complex natural scenes (Williford and von der Heydt, 2014). …”
Section: Introductionmentioning
confidence: 99%